Penerapan Logika Matematika Terhadap Permasalahan Sosial Uang Panai’ di Masyarakat Bugis-Makassar - Syafruddin Side; Hisyam Ihsan; Abdul Kadir (Journal of Mathematics, Computations and Statistics, 2019)
This research is categorized as pure research (a study of theory and implementation frommath logic) which is aimed to know more about social problem of Uang Panai’ in south sulawesi. Thisresearch conducted by collection data from respondent and then presented in the statements form wichwould be presented in math logic to determine the true value and conclude it. The result of this researchshowed some social cases of Uang Panai’ included the factors which caused the high cost of Uang Panai’and the effects of it (positive and negative effect).